The Bid by OpenChain to Transform The Supply Chain (Journal of Open Law, Technology & Society, 2018)
OpenChain aims at increasing open source compliance in the supply chain. This issue, which many initially dismiss as a legal concern or as low priority, is actually tied to making sure that open source is as useful as possible and has as little friction as possible. In a nutshell, because open source is about the use of third party code, compliance is the nexus of where equality of access, safety of use and reduction of risk can be found. OpenChain is built to increase trust between organiztions to accomplish this.  1This is an edited version of an article originally appeared on OpenSource.com